Data Logger Suhu Dan Tekanan Pada Smart Biogas Sampah Rumah Tangga Menggunakan MPX5500DP - Putri, Ratna Ika; Rifa'i, Muhammad; Anjarsari, Abella Novatna (Majalah Ilmiah Teknologi Elektro, 2020)
Abstract— The process of processing household waste into biogas is carried out using fermentation technology. Fermentation technology is the process of decomposition of organic compounds to produce energy and changes in the substrate become new products by microbes. In addition, the fermentation technique that has been done by fermenting household waste produces methane gas content (CH?). To process household waste into biogas is to use biodigester. Biogester is a closed space that is used for the waste fermentation process which is assisted by microbes. Using a biodigester is expected to accelerate the fermentation process of household waste into alternative biogas materials because of the airtight biodigester state. A temperature and pressure data logger tool is designed on smart biogas household waste using the MPX5500DP sensor. The MPX5500DP sensor will detect the amount of gas pressure from the biogas results because the range of readings from this sensor is in accordance with what is needed, while the DHT22 sensor uses a large temperature reading because the temperature in the biodigester is not too large between 28?C - 40?C. From the results of reading the temperature and pressure values, the data will be processed by the Arduino Uno Microcontroller and stored data by the data logger. Based on the test results, the temperature measurement error readings of 0.81%, while for the pressure measurement of about 3.5%.